The Influence of Teacher Performance Reviewed from Pedagogical Competence, Infrastructure, Motivation, and Job Satisfaction - Nita Dwi Risnawati; Sudarwati; Istiatin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to test and analyze pedagogical competence variables, infrastructure, motivation, and job satisfaction on teacher performance at SMP Negeri 1 Grogol Sukoharjo . This research method uses a quantitative descriptive research design. The population is all teachers of SMP Negeri 1 Grogol which amounts to 55 people. The sampling technique in this study is census technique or saturated sample as many as 55 people. Data retrieval using questionnaires and data analysis using SPSS 24.00 for multiple linear regression analysis calculations, F tests, t-tests, and determination coefficients. The results showed that pedagogical competence, infrastructure, motivation, and job satisfaction affect teacher performance. Based on statistical tests obtained adjusted R square (R2) of 86.9% which showed that 13.1% changes in teacher performance variables were explained by variables of pedagogical competence, infrastructure, motivation, and job satisfaction, while the remaining 13.1% were influenced by other variables that were not studied, such as leadership, discipline, and school culture.